Notas últimas sobre Piglia/Renzi - Laura Demaría (Cuadernos LIRICO)
This essay aims at reading the “last” literary work of Piglia/Renzi as a displaced quotation of the Escritos póstumos of Juan Bautista Alberdi, whith which Piglia kept a dialogue in Respiración artificial through the character of Enrique Ossorio. In the same way as it happened with Alberdi, there is now for Piglia an unpublished writings and recovered works publication plan; thus, his litterary work, supposed to have been brought to a close at the author’s death, begins or goes on again with those future papers. To think about Piglia’s work in that terms means to confirm its continuity and the successive order of his books, emphasizing the chronology. The article suggests, on the contrary, that the late texts of Piglia be read as if they would put into practice the idea of “last thinking” introduced by Oscar del Barco. Doing so, it discusses the concept of posthumous writings in Piglia’s work.